Tethering RNA to chromatin for fluorescence microscopy based analysis of nuclear organization - Pankert, Teresa; Jegou, Thibaud; Caudron-Herger, Maïwen; Rippe, Karsten (Methods, 2017)
Nuclear RNAs emerge as important factors to orchestrate the dynamic organization of the nucleus into functional subcompartments. By tethering RNAs to distinct genomic loci, RNA-dependent chromatin changes can be dissected by fluorescence microscopic analysis. Here we describe how this approach is implemented in mammalian cells. It involves two high-affinity protein-nucleic acid interactions that can be established with a number of different protein domains and DNA and RNA sequences. A prototypic system is described here in detail: It consists of the binding of MS2 bacteriophage coat protein to its RNA recognition sequence and the interaction between the bacterial LacI repressor protein to its target lacO operator DNA sequence. Via these interactions RNAs tagged with the MS2 recognition sequences can be recruited to a locus with integrated lacO repeats. By inducing RNA-chromatin binding a number of RNA-dependent activities can be dissected: (i) The RNA-induced compaction or decondensation of chromatin, (ii) identification of RNA-interacting chromatin modifiers that set epigenetic signals such as posttranslational histone modifications, and (iii) nuclear relocation of a genomic locus targeted by the tethered RNA. Thus, a variety of RNA-dependent activities can be evaluated with the MS2-LacI system, which are crucial for understanding how RNA shapes nuclear organization.